Ciberseguridad y protección de datos personales en el Perú - Quiroga León, José Álvaro (2021)
ADVOCATUS had the opportunity to interview José Álvaro Quiroga León, Peruvian lawyer specialized in Data Protection Law and cybersecurity. In the following lines he offers his opinions about the implementation of security measures and the importance of personal data protection within the framework of online transactions and interactions, the Regulations for the Application of the Personal Electronic Surveillance Measure approved by Supreme Decree N° 012-2020-JUS, among others.